Impaired Tubular Reabsorption Is the Main Mechanism Explaining Increases in Urinary NGAL Excretion Following Acute Kidney Injury in Rats. (28th February 2020) - Sancho-Martínez, Sandra M; Blanco-Gozalo, Víctor; Quiros, Yaremi; Prieto-García, Laura; Montero-Gómez, María J; Docherty, Neil G; Martínez-Salgado, Carlos; Morales, Ana I; López-Novoa, José M; López-Hernández, Francisco J
Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) is a secreted low-molecular weight iron-siderophore-binding protein. NGAL overexpression in injured tubular epithelia partly explains its utility as a sensitive and early urinary biomarker of acute kidney injury (AKI). Herein, we extend mechanistic insights into the source and kinetics of urinary NGAL excretion in experimental AKI. Three models of experimental AKI were undertaken in adult male Wistar rats; renal ischemia-reperfusion injury (IRI) and gentamicin (G) and cisplatin (Cisp) nephrotoxicity. Alongside standard histological and biochemical assessment of AKI, urinary NGAL excretion rate, plasma NGAL concentration, and renal NGAL mRNA/protein expression were assessed. In situ renal perfusion studies were undertaken to discriminate direct shedding of NGAL to the urine from addition of NGAL to the urine secondary to alterations in the tubular handling of glomerular filtrate-derived protein. Renal NGAL expression and urinary excretion increased in experimental AKI. In acute studies in both the IRI and G models, direct renal perfusion with Kreb's buffer eliminated urinary NGAL excretion. Addition of exogenous NGAL to the Kreb's buffer circuit, reestablishment of perfusion with systemic blood or reperfusion with renal vein effluent restored high levels of urinary NGAL excretion. Urinary NGAL excretion in AKI arises in large proportion from reduced reabsorption from the glomerular filtrate. Hence, subclinical cellular dysfunction could increase urinary NGAL, particularly in concert with elevations in circulating prerenal NGAL and/or pharmacological inhibition of tubular reabsorption. More granular interpretation of urinary NGAL measurements could optimize the scope of its clinical utility as a biomarker of AKI.